3a + (3b - 2a) + 5b =3a + 3b - 2a + 5b =(3a - 2a) + (3b + 5b) =a + 8b
The solution for the value of 3a would be -3. The equation would be 6a + 3(4) = 2.
add like terms: 3a -2a -5b + 6b +3b - 7b = a -3b
3A + 9B = 3(A + 3B)
3a+ax+3b+bx = 3(a+b)+(a+b)x = (a+b)(3+x)
1a+3b 2a+4b=3a +7b
-2a plus 3b
3a + 4b - (-6a) - 3b? There is no equivalent because you did not make it an equality. However you could combine the numbers... 3a + 4b +6a -3b = 9a + 1b
3a - 2b
Gathering like terms together, this is equal to 5a + 3b + 7c.
This expression can be factored. ab + 3a + b2 + 3b = a(b + 3) + b(b + 3) = (a + b)(b + 3)